Estresse hídrico induzido por soluções de PEG e de NaCl na germinação de sementes de nabiça e fedegoso - Pereira, Maria Renata Rocha; Martins, Cibele Chalita [UNESP]; Martins, Dagoberto [UNESP]; Silva, Rafael J. Navas da (My University, 2014)
The plants are subject to the conditions of multiple stresses, such as water and salt stress, which limit their development and their chances of survival. Aware of the factors that control seed germination can generate support for management strategies of weed species. The objective of this study was to evaluate the possible effects of water stress caused by PEG and NaCl solutions on germination of wild Raphanus raphanistrum and Senna obtusifolia seeds. The seeding was done with four repetitions of 50 seeds on moistened paper with solutions of polyethylene glycol (PEG 6000) and NaCl at osmotic potentials of 0.0, -0.2, -0.4 and -0.8 MPa. The germination test was conducted at 25° C in the presence of light, evaluating the first test score to seven days after sowing, and weekly, germination (normal seedlings) until 35 days; it was also calculated the index germination rate. The results allowed the conclusion that water stress by PEG causes a greater reduction in force, speed of germination and accumulated germination of seeds of Raphanus raphanistrum and Senna obtusifolia seeds. The Senna obtusifolia was more tolerant to water stress.
Saline water stress and the germination of seeds of Raphanus raphanistrum and Senna obtusifolia
Keywords: Osmotic potential; Salinity; Vigor; Weeds